Rekurence primárních chorob po transplantaci jater - Žampachová, Víta; Honsová, Eva (Ceskoslovenska patologie, 2015)
A majority of primary diseases for which orthotopic liver transplantation is carried out may recur in the liver allograft, mostly in adults. As the indication criteria, transplantation surgery and post-transplantation care improve, the patients survival lengthens as well, leading to concurrently increasing incidence as well as an increase in the relevance of recurrent diseases, which are the most significant cause of late liver graft dysfunction. The frequency, clinical consequences and therapeutic options of different disease recurrence vary considerably. Even recently the worst prognosis has been associated with hepatitis C for 100% reinfection, this situation is beginning to change with new oral antiviral drugs, as has already been successfully done with hepatitis B. Among immune-mediated disorders, primary biliary cirrhosis recurrence affects 30 - 50% of transplant patients, albeit with mild consequences. Graft loss and subsequent necessity of retransplantation are observed in almost 10% of patients with primary sclerosing cholangitis recurrence. 30% prevalence rates for autoimmune hepatitis recurrence are reported but the frequency of graft loss has declined considerably due to maintenance of corticosteroid therapy. Excessive relapse of alcohol consumption in patients with liver transplant for alcoholic liver disease leads most commonly to extrahepatic complications. Recurrent non-alcoholic steatohepatitis is rarely connected with graft loss in 5 - 10 years after transplantation. The diagnosis of a recurrent disease following liver transplantation is to a large extent based on histopathological features. In the differential diagnosis, other causes of graft dysfunction must be excluded.
Keywords: transplantace jater; liver transplantation - recurrence - biopsy.; nemoci jater; Humans; Liver Diseases; Recurrence; reoperace; Liver Transplantation; recidiva; Reoperation; lidé